Measuring quality of C2C E-commerce websites in Lao PDR - Bounthanome Vilaysuk (2018)
© Springer Nature Singapore Pte Ltd. 2019. E-commerce gives chances to businesses of all sizes to compete globally. It opens the doors to new product, services, and creates opportunities. Though e-commerce was made possible 25 years ago, it is relatively new in Lao PDR. Merely 12.8% of firms owns website. Lao government’s recent development in infrastructure and policy, in conjunction with cooperative agreement with developed countries, presents a promising future for e-commerce. One key success factor for e-commerce is service quality. A high-quality website draws customer and leads to purchase. This study proposes an improvement to ES-QUAL, a framework for electronic service quality, to address missing quality dimensions and adaption for quality measurement of C2C websites in Lao PDR.